THE EFFECT OF PROVIDING A COMBINATION OF LOW IMPACT AEROBIC EXERCISE AND KERONCONG MUSIC THERAPY TO IMPROVE THE QUALITY OF SLEEP IN THE ELDERLY IN SEMBUHAN LOR HAMLET OF SLEMAN - Robbani, M. Satria; Moh. Ali Imron (Journal of Innovation Research and Knowledge, 2024)
Background: Older people can be defined as a group entering the final stages of life, starting with the middle age 60 to 74 years, the elderly aged 75 to 90 years, and the ancient age more than 90 years. The increase in the global prevalence of sleep disorders in the elderly, especially in Africa and Asia, is around 150 million people. The increase in the prevalence of sleep quality disorders in the elderly in Indonesia is very high, namely 67%. Based on this background, researchers are interested in finding out the effect of combining low-impact aerobic exercise and keroncong music therapy to improve sleep quality in older people in Padukuhan Semuhan Lor, Sleman. Research Objective: Therefore, this study aimed to determine how combining low-impact aerobic exercise and keroncong music therapy improves sleep quality in older people in Padukuhan Semuhan Lor, Sleman. Method: This research is an experimental quantitative research with a two-group pre-test and post-test approach. The sampling technique used in this research was purposive sampling with a total sample of 40 subjects. The instrument in this study used the Pittsburgh Sleep Quality Index observation. Results: The results of the analysis of variables using the Wilcoxon Sign Paired T-Test and Mann Whitney U-Test stated that there was an effect of giving a combination of low-impact aerobic exercise and keroncong music therapy to improve sleep quality in older people by 0.001 (p0.05). Conclusion: There is a difference in the effect of giving a combination of Aerobic Exercise low Impact and Aerobic Exercise low Impact + Music Therapy on improving sleep quality in the elderly. Aerobic Exercise low Impact + Music Therapy has a greater effect on improving sleep quality in the elderly. Suggestion: For further researchers, the results of this study can be used as a review of data related to aerobic exercise low impact + music therapy to improve and in further research it is recommended to use male respondents as a comparison.